Moral uncertainty and the farming of human-pig chimeras - Koplin, J; Wilkinson, D (BMJ Publishing Group, 2019)
It may soon be possible to generate human organs inside of human-pig chimeras via a process called interspecies blastocyst complementation. This paper discusses what arguably the central ethical concern is raised by this potential source of transplantable organs: that farming human-pig chimeras for their organs risks perpetrating a serious moral wrong because the moral status of human-pig chimeras is uncertain, and potentially significant. Those who raise this concern usually take it to be unique to the creation of chimeric animals with ‘humanised’ brains. In this paper, we show how that the same style of argument can be used to critique current uses of non-chimeric pigs in agriculture. This reveals an important tension between two common moral views: that farming human-pig chimeras for their organs is ethically concerning, and that farming non-chimeric pigs for food or research is ethically benign. At least one of these views stands in need of revision.